(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The analysis of surveys conducted in Bulgarian companies proves that the quantity and quality of human capital to the greatest extent determine the long-term potential for sustainable organizational development. Aware of the need for investment in human capital, more and more company leaders and managers are focused on creating value for their business through training and development of their employees; building knowledge, skills, competences and motivational attitudes towards the changing working environment in Industry 4.0. The article examines flexible forms of work and creative approaches to increasing the satisfaction and engagement of employees in the implementation of strategic company goals.